Impaired Implantation and Hereditary Thrombophila; Expression of LIF (Leukemia Inhibitory Factor) on Extravillous Trophoblasts - Hekimoğlu, Rümeysa; Pergin, Atilla; Uğur, Yeşim; Beksaç, Sinan; Turğal, Mert; Çakar, Nur (Gynecology Obstetrics & Reproductive Medicine, 2012)
OBJECTIVE: LIF (Leukemia İnhibitory Factor) was shown to have an important role in implantation. The aim of this study is to investigate the expression of LIF on extravillous trophoblasts in normal pregnancies and pregnancies with MTHFR (methylenetetrahydrofolate reductase) mutations. This study was also designed to demonstrate the “impaired implantation based” perinatal complications such as early pregnancy losses in pregnancies with hereditary thrombophilia (MTHFR 677 & 1298 mutations; homocystinemia and impaired folat/vitamin B12 metabolisms). STUDY DESIGN: Abortus material until 10th gestational-week were used in this study. The patients were divided into 2 groups as: Group 1; control group (unwanted induced abortions), Group 2; abortus material from pregnancies with hereditary thrombophilia. Hereditary thrombophilia cases were consisted of only MTHFR homozygote mutations (MTHFR 677 & 1298). Indirect ABC (avidin-biotin-peroxidase complex) was applied to all of the abortus material to investigate the expression of LIF. RESULTS: Expression of LIF in extravillous trophoblasts was immünohistochemically stronger (+++) in MTHFR group than the extravillous trophoblasts of the control group (++). This finding was also found to be statistically significant (p≤ 0.05). CONCLUSION: The impaired LIF expression of extravillous trophoblastic cells in MTHFR patients can be one of the reasons of early fetal losses due to impaired implantation. Direct affect of homocystinemia, cell degragates of maternal endothelial cells due to injury and thrombosis and activation of complement system may be the reasons of defective LIF synthesis. Defective LIF expression on extravillous (interstitial) trophoblasts may result in insufficient activation of the LIF receptors in the decidua and limiting their migration during placentation. On the other hand, number of the extravillous trophoblasts developing from cytotrophoblasts may also be negatively affected by the disturbed LIF expression resulting in a shallow placenta.